Utilization Of Used Goods As A Biomath Learning Media - Purba, Yoel October; Sihite, Julius Martunas Sihite Martunas; Sinaga, Hotmida Sinaga; Siahaan, Kevin William Andri; Yunita, Widia (UIN Fatmawati Sukarno Bengkulu, 2022)
Utilization of used goods in the environment can be used as a learning medium to trigger the creativity of students in learning and learning activities. Learning media is very influential in the implementation of the learning process, it is because students are more sensitive to see clearly than the learning material. This study aims to describe: 1) Biomath learning media obtained from used goods in the environment; 2) Simple learning media as a way to improve students' understanding of the lesson; 3) Utilization of used goods as a form of environmental care. This research was conducted in 2 cycles, each cycle consisting of four stages, namely: (1) planning, (2) implementing actions, (3) observation, and (4) reflection. The type of data collected is qualitative data in the form of observations of teacher and student activities during the teaching and learning process, and quantitative data in the form of student learning outcomes through the final evaluation test of the action. The results of this research are expected to be used by educators as a reference for obtaining learning media from used goods in the surrounding environment, so as to create varied learning with learning media that builds enthusiasm for learning and creates learning comfort to create those who can explore themselves with various things. new close to his world